INOVASI METODE PENGAJARAN BAHASA INDONESIA DALAM MENGHADAPI TANTANGAN TEKNOLOGI INFORMASI DAN ERA DIGITAL - Asep Saepurokhman; E. Sulyati (CV. ADIBA AISHA AMIRA, 2026)
This study aims to examine innovations in Indonesian language teaching methods in response to the challenges posed by information technology development and the digital era. The rapid growth of digital technology has transformed the learning environment, requiring Indonesian language teaching to move beyond conventional teacher-centered methods toward more interactive, collaborative, creative, and technology-based approaches. This study uses a library research method by reviewing relevant books, journal articles, policy documents, and academic sources related to Indonesian language learning, digital literacy, educational technology, TPACK, multimodal texts, and artificial intelligence in education. The data were analyzed using content analysis to identify key concepts, research trends, and theoretical perspectives relevant to the topic. The findings show that innovation in Indonesian language teaching can be implemented through digital literacy integration, blended learning, flipped classroom, project-based learning, gamification, multimodal text production, and the ethical use of artificial intelligence. These methods are considered capable of improving students’ reading, writing, speaking, listening, critical thinking, creativity, and digital communication skills. However, the effectiveness of these innovations depends on teachers’ digital competence, infrastructure readiness, institutional support, and students’ ethical awareness in using technology. The study concludes that Indonesian language teaching in the digital era should not only focus on linguistic competence but also strengthen digital literacy, communication ethics, creativity, and critical thinking. Therefore, innovative teaching methods are essential to create adaptive, meaningful, and relevant Indonesian language learning in the context of technological transformation.